Insights into the cyanosphere: capturing the respective metabolisms of cyanobacteria and chemotrophic bacteria in natural conditions?. Issue 3 (24th March 2021) - Pascault, Noémie; Rué, Olivier; Loux, Valentin; Pédron, Jacques; Martin, Véronique; Tambosco, Jennifer; Bernard, Cécile; Humbert, Jean‐François; Leloup, Julie
Abstract: Specific interactions have been highlighted between cyanobacteria and chemotrophic bacteria within the cyanosphere, suggesting that nutrients recycling could be optimized by cyanobacteria/bacteria exchanges. In order to determine the respective metabolic roles of the cyanobacterial and bacterial consortia (microbiome), a day–night metatranscriptomic analysis was performed on Dolichospermum sp. (N2 ‐fixer) and Microcystis sp. (non N2 ‐fixer) natural blooms occurring successively within a French peri‐urban lake. The taxonomical and functional analysis of the metatranscriptoms have highlighted specific association of bacteria within the cyanosphere, driven by the cyanobacteria identity, without strongly modifying the functional composition of the microbiomes, suggesting functional redundancy within the cyanosphere. Moreover, the functional composition of these active communities was driven by the living mode. During the two successive bloom events, it appeared that NH4 + (newly fixed and/or allochthonous) was preferentially transformed into amino acids for the both the microbiome and the cyanobacteria, while phosphate metabolism was enhanced, suggesting that due to a high cellular growth, P limitation might take place within the cyanosphere consortium.